Analysis of mammalian gene batteries reveals both stable ancestral cores and highly dynamic regulatory sequences - Ettwiller, Laurence; Wittbrodt, Joachim (Genome biology, 2008)
Changes in gene regulation are suspected to comprise one of the driving forces for evolution. To address the extent of cis-regulatory changes and how they impact on gene regulatory networks across eukaryotes, we systematically analyzed the evolutionary dynamics of target gene batteries controlled by 16 different transcription factors.